A two‐step method for 4‐pin form‐closure gripper with grasping force optimization. Issue 5 (15th April 2021) - Li, Rui; Li, Yinlin; Su, Xiaojie
Abstract: Grasp planning and the grasping force optimization are challenging issues associated with the dexterous robotic hand grasping problem. To ensure a safe, fast, and stable grasp for robots, careful determination of the grasping points and the grasping forces is required. The former creates an open question because of the availability of multiple solutions. The latter is formulated as a problem for minimizing an objective function subject to form‐closure constraints and balance constraints of external forces. In this work, we propose a novel approach for the grasping force optimization of the 4‐pin environmental constraint‐based form‐closure grasp using dynamic neural networks. To find a form‐closure grasp, we propose an environmental constraint‐based algorithm and convert it to a problem of finding the local minima of a constraint region, resulting in an easy determination of the grasping points with the guarantee of grasping safety. To satisfy the grasping force limit of the contact points, we solve the grasping force optimization problem with friction constraint, which maximize the efficiency of the applied force and power of the dexterous hand. The proposed approach is evaluated with 4‐pin gripper, and the result demonstrates that we can plan a safe, fast, and stable grasp from any initial state to a form‐closure grasping state.